Precedent in Pakistani law - Munir, Muhammad (Oxford University Press, 2014)
In the Common Law system, it is the doctrine of 'precedent' which courts depend upon, more than any other legal doctrine, while arriving at their decisions. The elements that constitute the doctrine of precedent are numerous and complex.